Identifying geogenic and anthropogenic controls on different spatial distribution patterns of aluminium, calcium and lead in urban topsoil of Greater London Authority area. (January 2020) - Meng, Yuting; Cave, Mark; Zhang, Chaosheng
Abstract: Quantifying variation of metals in urban soils is crucial for efficient environmental and public health management. Prior to the interferences of human activities, regional topsoil geochemical distributions were generally primarily controlled by the underlying parent materials (PMs). With the rapid urbanisation, urban topsoil geochemical distributions have been modified with different levels. Three metals, aluminium (Al), calcium (Ca) and lead (Pb), were chosen to investigate the different levels of geogenic and anthropogenic controls in urban topsoil of Greater London Authority (GLA) area. These three metal elements clearly demonstrated the different spatial distribution affected by human activities using analysis of variance (ANOVA) and GIS-based spatial analysis. The high values of Al were in the clay which is located in the north and south GLA area; Pb accumulated in built-up areas and near traffic roads, which was likely associated with leaded paints and leaded petrol, respectively; the high Ca concentrations were in the Chalk bedrock of the southern GLA area and historical deconstruction and reconstruction sites in the city centre. Based on spatial interpolation and hot spot analysis (local Moran's I), this study reveals the different levels of geogenic and anthropogenic controls on different chemicals in urban soils: while the spatial distribution of Pb, which is more easily affected by human activities, can be significantly changed, the inert element Al may still be able to maintain its natural spatial distribution even in the heavily urbanized GLA area, and Ca demonstrates the mixed spatial distribution affected by both natural factors and human activities. Highlights: Spatial analyses were useful in identifying spatial patterns of urban geochemistry. Different levels of geogenic and anthropogenic controls found on different chemicals. Al was mainly controlled by geology, elevated in clay areas. Pb was mostly under anthropogenic control, elevated in built-up area and near road. Ca was impacted by both geogenic and anthropogenic controls.